Pengaruh Waktu Karbonisasi Terhadap Kadar Air dan Abu Serta Kemampuan Adsorpsi Arang Tempurung Nipah Teraktivasi Asam Klorida - Theresia Evila Purwanti Sri Rahayu; Rosita Dwityaningsih; Ulikaryani (P3M Politeknik Negeri Cilacap, 2022)
The Cilacap region, Central Java, Indonesia is a coastal area that is overgrown with nipa palm trees, making it one of the potential local natural resources to be exploited. Utilization of this plant has been carried out for the fields of food, energy, clothing, pharmaceuticals, and furniture, but as an anode material for lithium-ion batteries is still being researched. Studies on lithium-ion batteries in Indonesia in particular have not started long ago so that research in this field is still limited and few in number, but the development of lithium-ion batteries has become one of the national research priorities in the field of new and renewable energy sources as stated in the Indonesian national research master plan (RIRN) for the period 2017 – 2045. This study was conducted to examine the potential feasibility of activated charcoal from nipah shells as anode material for lithium-ion batteries. The feasibility test parameters studied in this study include water content, ash content and adsorption capacity stated as iodine and methylene blue number which are the basic characterizations for activated charcoal referring to SNI 06-3730-1995. The nipah shell carbonization process was carried out in the presence of oxygen at an optimized temperature of 210 oC with a 1 hour time interval variation from 3 to 8 hours, followed by an activation process using a strong acid, namely HCl with a concentration of 2 M. The experimental results showed the average value of moisture content, ash content, iodine, and methylene blue number are 12.5%, respectively; 1.75%; 2515.9161 mg/g; and 97%, all of which are above the quality standard values, so the conclusion from this study is that activated charcoal from nipah shell has basic characteristics that have the potential to be further developed, including as raw material for lithium-ion battery anodes.